If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 24 + -3x Solving 15 = 24 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 15 + 3x = 24 + -3x + 3x Combine like terms: -3x + 3x = 0 15 + 3x = 24 + 0 15 + 3x = 24 Add '-15' to each side of the equation. 15 + -15 + 3x = 24 + -15 Combine like terms: 15 + -15 = 0 0 + 3x = 24 + -15 3x = 24 + -15 Combine like terms: 24 + -15 = 9 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| x^3-10x^2+21x-30=0 | | 3y-10x-22=15x-4y+31 | | 3x+114=9x-12 | | 133-2x=34x+17 | | (3z-4)(6+z)=0 | | 6x+8=-122-9x | | 183-2x=43x+23 | | 9-10x=209-45x | | 2x+3(x-5)=5(2x-3) | | 2mn+9mp= | | 4(x+3)-7x=6 | | 10-3x+8=30+2x+48 | | 17x+8=42 | | 9x-6-5x=8+x-14 | | 56-6x=3x+21 | | 5-7x=3x+21 | | -70-9x=43-21x | | (5y-2)=52 | | 14-8x+6-5x=10+2x-5 | | 6x+18=116-6x | | (x+2)(2-x)=6x-x | | 2x+36=21x-36 | | 17-6x=4x-8 | | 9-5k+2k=k-23 | | x^2+4x-1=9x-5 | | 6x+30=13-33 | | x^2+8x-2=7 | | x^2-(a+2b)x+b^2+ab=0 | | 24a=36 | | 12-x=30-4x | | 3x+4=5x-16 | | x^2+32x-196=0 |